Hidden hemorrhage: A case of idiopathic omental hemorrhage causing spontaneous hemoperitoneum - Emily McDowell; Kirsten Hughes; Max Jones BS; Candace Kimpson; Michael J. Twiner; Sean McCormick (Journal of the American College of Emergency Physicians Open)
Abstract Idiopathic omental hemorrhage (IOH) is a rare and underexplored entity in current medical literature. Most patients are male, aged 20–65 years, presenting with abdominal pain. Like most presentations of active intra‐abdominal bleeding, recognition, stabilization, and definitive management are key. Expedited diagnosis and treatment of this condition is imperative as mortality rates can exceed 30% in cases due to delays of care. Presented here is a case of a young male with abdominal pain and recurrent emesis, ultimately diagnosed with bleeding from the greater omentum. He had been discharged from the emergency department the previous day. This patient's presentation highlights the importance of having high clinical suspicion for IOH in patients with recurrent or intractable nausea and emesis with persistent abdominal pain and utilizing advanced imaging for unexplained symptoms.